Stres Akademik Siswa Full Day School di SMA N 1 Ampek Angkek - Ridhati, Istiqamah; Putriani, Lisa (Lembaga Yasin AlSys, 2024)
Academic stress is a condition where there is a mismatch between school demands and students' abilities so that students are burdened by various school or academic demands. The reality in the field is that there are students who experience academic stress in following the teaching and learning process at school, plus now many schools have implemented a full day school learning system, which makes students spend more time at school. This study aims to describe the academic stress of full day school students in high school from physical responses, emotional responses and behavioral responses.This type of research is quantitative research with a descriptive approach. This research was conducted at SMA N 1 Ampek Angkek, with a population of 680 students and a sample of 282 students. Data was obtained by providing research instruments in the form of questionnaires to students. The results of the study were processed to find the percentage and then categorized according to the level of academic stress.The results of the study revealed that, first, the academic stress of SMA N 1 Ampek Angkek students was in the moderate category with a percentage of 43%. This means that SMA N 1 Ampek Angkek students have not been able to control the situation or conditions that cause stress related to academics. Second, academic stress of students related to physical responses is in the moderate category, Third, academic stress of high school students related to emotional responses is in the high category. Fourth, academic stress of high school students related to behavioral responses is in the high category. The implications in guidance and counseling services such as providing information services, individual counseling services, group guidance services and group counseling services.